2011
DOI: 10.1603/ec10330
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vineyard Pesticides on a Beneficial Arthropod, Typhlodromus pyri (Acari: Phytoseiidae), in Laboratory Bioassays

Abstract: Laboratory bioassays were conducted to evaluate the effects of six vineyard pesticides on Typhlodromus pyri Scheuten (Acari: Phytoseiidae), a key predator of the mite Calepitrimerus vitis Nalepa (Acari: Eriophyoidae), in Pacific coastal vineyards. Materials tested were whey powder, 25% boscalid + 13% pyraclostrobin (Pristine), 40% myclobutanil (Rally), micronized sulfur (92% WP), 75% ethylene bisdithiocarbamate (mancozeb; Manzate), and 91.2% paraffinic oil (JMS Stylet), all applied at three concentrations. Pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 36 publications
0
19
0
3
Order By: Relevance
“…However, wettable sulfur was not effective against the leafhopper Erythroneura elegantula Osborn (Hemiptera: Cicadellidae) [36]. In vineyards, negative side effects of sulfur dust on natural enemies, including phytoseiid mites, have also been observed [36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…However, wettable sulfur was not effective against the leafhopper Erythroneura elegantula Osborn (Hemiptera: Cicadellidae) [36]. In vineyards, negative side effects of sulfur dust on natural enemies, including phytoseiid mites, have also been observed [36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a report on the use of fungicides in the European Union over the period 2001–2003 indicated that while viticulture only accounted for 3.3% of the agricultural area, a staggering 81,000 tonnes of active substance were applied annually to grapevines in European vineyards, which represented 67% of all fungicides applied to crops in the EU 3 . Not only does this translate into increased production costs for growers, but there is also the potential impact of these chemicals on the health of beneficial organisms in the vineyard 4 and vineyard workers 5 , as well as increased carbon emissions generated from their frequent application. Thus, the integration of effective genetic resistance into grape cultivars would reduce the dependence of viticulture on chemical inputs, leading to significant financial, health, and environmental benefits.…”
Section: Introductionmentioning
confidence: 99%
“…O crescimento populacional de C. vitis no vinhedo varia conforme as condições climáticas, com a composição e a quantidade de ácaros predadores e ainda com os tratamentos fitossanitários realizados (DUSO; VETTORAZZO, 1999;GADINO et al, 2011). Em condições de temperatura constante, o tempo de uma geração de C. vitis varia de 5,5 dias a 28 e 30ºC até 17,5 dias a 17ºC, enquanto a fecundidade oscila de 0,2 ovo a 17ºC até 26,1 ovos a 25ºC, com possibilidade de até 14 gerações desta espécie por estação de crescimento (WALTON et al, 2010).…”
Section: Introductionunclassified